OPTIMALISASI PEMASARAN PRODUK LOKAL WARGA DUSUN PULAU NANGKA MELALUI PLATFORM MEDIA SOSIAL TIKTOK - Claudia, Sindi; Iqbal Arrosyad, Muhammad; Amal, Fadilah; Saputra, Kevin Saki; Ma'arif, Ilal; Istahara, Istahara; Fauzan, Fauzan; Rahmadika, Dhevario; Alifah Iswarini, Rifdah; Alwijah, Alwijah; Lastari, Fetty (Yayasan Education and Social Center, 2025)
The development of digital technology has presented various opportunities for local business actors to expand their market reach. One of the increasingly popular social media platforms in marketing strategies is TikTok, which offers creative features and algorithms based on user interests. This study aims to analyze the implementation of TikTok as a marketing medium to increase the selling power of local products of Dusun Pulau Nangka residents. The methods used in this study include observation, interviews, and analysis of digital content strategies implemented by local business actors. The results of the study show that optimal use of TikTok, through the creation of creative content, the use of advertising features, and active interaction with users, can increase product visibility and consumer appeal. With the right marketing strategy, Dusun Pulau Nangka local products can be better known, thereby encouraging economic growth in the local community.